An Investigation into some Soil Indices as Indicators of High Soil Erodibility in Anambra State Southeastern, Nigeria - Romanus Udegbunam Ayadiuno, Dominic Chukwuka Ndulue (International Journal of Modern Agriculture, 2021)
An Investigation into some soil indices as indicators of high soil erodibility in Anambra State Southeastern, Nigeria looks at the phenomenon from the soil indices perspective. The study identified some soil variables through the analysis of soil samples extracted from different selected areas of the study and their various levels of predictions and contributions to soil erodibility in the study area. The variables are fine sand, coarse soil, silt and clay (particle size distributions), mean weighted diameter (MWD), aggregate stability, soil porosity, organic matter content, Atterberg limits, among others. Primary and secondary data were used for the study, which include geo-physical field visit, measurements, surveys and observations; Satellite imagries, topographic maps, published and non published literatures. Regression analysis was done in SPSS version 25 and the result shows that the model is significant at 0.018 and predicts their various contributions to the dependent variable. The study concludes that the soil analysis result shows the soils across the area to be are highly erodible and prone to erosivity at the dispersion rate (DR) value ranging from 0.429% to 0.865%, assuming soils with a dispersion rate greater than 0.15% are erodible in nature. Soils with low organic matter content are more vulnerable or susceptible to high soil erosivity. Based on the fact that organic matter increases soil stability, the study therefore recommends mulching, cover cropping and re-vegetation of all available bare spaces in the study area; adding organic matter content to the soil which will increase bonding and reduce the direct hitting of raindrop on the soil surfaces thereby reduces the dislodgement of these soils.